Population structure of three New Zealand crested penguins identifies current conservation challenges for the Fiordland penguin/tawaki, erect-crested penguin, and eastern rockhopper penguin - Jeff White; Philip Lavretsky; Pablo Garcia Borboroglu; Alexis Díaz; Ursula Ellenberg; David Houston; Robin Long; Thomas Mattern; Herman L. Mays; Klemens Pütz; Philip J. Seddon; Kevin G. McCracken (PLoS ONE, 2025)
Identifying contemporary population structure and genetic connectivity among seabird populations is essential for developing conservation plans for threatened species, especially as factors like philopatry, non-breeding behavior, and oceanographic features might limit gene flow between isolated populations and influence changes in genetic diversity over time. Here, we characterize the population structure of three closely related crested penguin species in New Zealand: Tawaki (Eudyptes pachyrhynchus; Fiordland penguins), erect-crested penguins/tawaki nana hī (Eudyptes sclateri), and eastern rockhopper penguins/tawaki piki toka (Eudyptes filholi). Whereas tawaki populations appear to be stable, the erect-crested and eastern rockhopper penguin populations have seen dramatic declines in the recent historical record. To understand the genetic implications of these differences in population trajectories, we assessed genetic connectivity among multiple colonies using thousands of nuclear autosomal loci. Our results indicate that tawaki are a single, genetically diverse population without colony-based structure, which is consistent with the currently observed stable or increasing population of tawaki. However, conservation efforts should continue to prioritize protecting marine habitats to safeguard this species. In contrast, we identified two genetically distinct populations of erect-crested penguins corresponding to the Antipodes Islands and the Bounty Islands groups. The Antipodes Islands eastern rockhopper population exhibited high levels of coancestry and low genetic diversity, consistent with population decline and limited immigration. The lack of gene flow and genetic diversity in both erect-crested and eastern rockhopper penguins on the Antipodes Islands raises concerns and highlights the need for continued research to identify the causes of declines to inform conservation efforts of these penguins.